Developing business English communication skills and intercultural competence: a student-centred approach - Simões, Anabela Valente (2021)
Communication is the cornerstone of organizational life, either at an internal level or exogenously (Kunsch, 2009). As organizations expand internationally, having to interact with transcontinental intermediaries, distinct government agencies and institutions (Brannen et al., 2017) or company foreign representatives, an adequate level of linguistic competence is likely to play an even more significant role in facilitating or hampering any global operation (Schomaker et al., 2014). As language and culture go hand in hand, in today’s globalised world it is also of paramount importance to develop cultural sensitivity. According to Landau (2018), it is not just helpful to business but a recognized essential, since businesses that understand and accommodate individuals from different cultural backgrounds are better equipped to scale and build a better reputation amongst their competitors. With over 1.5 million speakers worldwide (Lustig, 2018), English has become not only the language of science and technology (Brock-Utne, 2016) but also the global language of business. The awareness that communicative competence in English is crucial in today’s labour market is reflected in the study programme design of the 1st cycle degree in Office Management and Business Communication (OMBC) held at the University of Aveiro (UA), which includes five 60-hour courses of Business English: English Language (1st semester), English Translation and Terminology (2nd semester), English Language and Business Communication (3rd semester), English Documentation (4th semester), and English Language and Organizational Culture (5th semester). Literature demonstrates that student-centred learning environments, where practical and more realistic assignments can be developed, are likely to be more effective and conducive to a greater level of development of both technical and interpersonal skills (Severiens et al., 2015). Bearing this view in mind, the present paper aims to describe two project-works developed within two OMBC courses: English Language and Business Communication and English Documentation. In their first assignment (1st semester, 2018/19), students were called to develop research on a country of their choice, analyse it through Hofstede’s 6-D model, allocate it to Hall’s high-/low-context cultures and identify each country’s specific characteristics in terms of business etiquette. The results of their research, whose main purpose was the development of students’ intercultural business communication skills, were displayed in poster format and presented to the class, simulating a conference setting. In their second project-work (2nd semester, 2018/19), those same students were challenged to conduct research on the impact of digital transformation (DT) on organizations, one of the topics of their syllabus, and again exhibit their findings in a scientific poster ― this time not having the classroom as venue, but in the context of a conference on DT organized at the UA. After following the regular procedures of an abstract and poster submission, selected students had the opportunity to present their assignment in a real scientific event, to their peers and to conference participants. In addition to the detailed description of the project-works, this paper also aims to present the results of a survey on students’ perception of the activities. The gathered data indicates that both technical and interpersonal competences were successfully addressed.